ESTUDO DA LIXIVIAÃ‡ÃƒO DO FÃ“SFORO EM CINCO SOLOS DO MUNICÃPIO DE PIRACICABA - RovÃ©ri, Maria de FÃ¡tima Silva; Miyada, Waldomiro Shigueru; Mello, Francisco de Assis F. de; Silveira, Ronaldo Ivan (REVISTA DE AGRICULTURA, 2020)
ESTUDO DA LIXIVIAÃ‡ÃƒO DO FÃ“SFORO EM CINCO SOLOS DO MUNICÃPIO DE PIRACICABA